2013
DOI: 10.1002/fsn3.56
|View full text |Cite
|
Sign up to set email alerts
|

In‐house–validated liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method for survey of acrylamide in various processed foods from Korean market

Abstract: Acrylamide (AA) is a chemical found in starchy foods that have been cooked at high temperatures. The objective of this study is to monitor the levels of AA in a total of 274 samples of potato chips, chips (except potato chips), biscuits, French fries, breakfast cereals, chocolate products, tea, seasoned laver, and nut products sampled in Korean market. These processed foods include (1) potato chips, (2) chips (except potato chips), (3) biscuits, (4) French fries, (5) breakfast cereals, (6) chocolate products, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Levels of acrylamide in 274 processed foods from Korean markets reported by Lee et al. () were as high as 1,435 μg/kg, with potato chips containing the highest amounts and nut product the lowest amounts. Zając et al.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Levels of acrylamide in 274 processed foods from Korean markets reported by Lee et al. () were as high as 1,435 μg/kg, with potato chips containing the highest amounts and nut product the lowest amounts. Zając et al.…”
Section: Introductionmentioning
confidence: 89%
“…The acrylamide levels in 56 Italian biscuits and breakfast cereals ranged from 30 to 940 μg/kg (Capei, Pettini, Lo Nostro, & Pesavento, 2015). Levels of acrylamide in 274 processed foods from Korean markets reported by Lee et al (2013) were as high as 1,435 μg/kg, with potato chips containing the highest amounts and nut product the lowest amounts. Zając et al (2013) found that the average acrylamide intake (in μg/kg bw/day) in Poland was 0.85 ± 0.82, but that young individuals consume 2.24 times more acrylamide than older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Some of our AA data (274 processed foods) for the 485 processed foods were previously published [ 22 ], whereas the rest of the data were reported by the Korea Food and Drug Administration [ 23 ]. The concentration of AA in 485 food samples, including potato crisps, crisps (other than potato crisps), biscuits, French fries, coffee, bread, cakes, breakfast cereals, chocolates products, cocoa products, nuts and nut products, juice, tea products, kimchi, and dried and roasted seaweed were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…As the pretreatment is effective for the complex tea matrix, it also works well in different types of food with minor modification [4][5][6][7][8][9][10][11]. As the pretreatment is effective for the complex tea matrix, it also works well in different types of food with minor modification [4][5][6][7][8][9][10][11].…”
Section: Synopsis Of Analytical Techniquesmentioning
confidence: 99%
“…Unfortunately, different amounts of acrylamide in tea and tea drinks were discovered by the survey of acrylamide levels in Asian foods [4][5][6][7][8][9][10][11][12][13]. The Maillard reaction has been shown to be the main pathway for acrylamide formation in a wide range of foods containing important precursors, mainly asparagine and reducing sugars, processed at high temperatures [14][15][16].…”
Section: Introductionmentioning
confidence: 99%